ANALISIS PEMAHAMAN MAHASISWA JURUSAN BAHASA INGGRIS POLITEKNIK TONGGAK EQUATOR TERHADAP PENGGUNAAN FRASA VERBAL - Magpika Handayani (tuahtalino, 2018)
Phrasal verb is one of the important components in the process of learning a foreign language. It is one form of vocabulary in the collection of words that make up the phrase where the verb is the word that heads the phrase. Students can not interpret phrasal verb partially but it must be interpreted collectively. The understanding of Politeknik of Tonggak Equator Pontianak sudents toward phrasal verb need to be known considering many literatures and terms used in the teacing and learing process. In doing this research, the method used is descriptive by describing the condition of students through recording their activity and identifies problems in using phrasal verb. Techniques of data collecting are interviews and tests to obtain a description of students understanding of the use of phrasal verb. Filling in the blank form of test is used in order to know the understanding of students toward the use of phrasal verb in sentence, while interviews conducted to match test answers with oral answers. Some students still have difficulty in understanding the phrasal verb. Students are still fixated on sentence patterns and think that phrasal verb is a phrase that can be translated word by word.